Temperature threshold for preferential bubble formation on grain boundaries in tungsten under in-situ helium irradiation. (15th April 2020) - El-Atwani, O.; Cunningham, W.S.; Perez, D.; Martinez, E.; Trelewicz, J.R.; Li, M.; Maloy, S.A.
Abstract: Understanding a material's radiation tolerance requires examining its performance under different irradiation conditions. Here, we investigate the radiation tolerance in terms of helium bubble damage in tungsten irradiated in-situ with 16 keV helium at 1073 K and 1223 K. Damage evolution represented by helium bubble density, size and total change in volume in the grain matrices and the grain boundaries are quantified as a function of fluence. Preferential large bubble formation and a higher change in volume on the grain boundaries occurred at 1223 K, suggesting faster migration of certain helium-vacancy complexes as confirmed by a diffusion-reaction model. Graphical abstract: Image, graphical abstract